2009
DOI: 10.2174/1874920800902010054
|View full text |Cite
|
Sign up to set email alerts
|

A Fourteen Year Follow-Up Study of Health Promoting Schools in Norway: Principals` Perceptions of Conditions Influencing Sustainability

Abstract: Abstract:In this study, we examined the sustainability of health-promoting practices in Norwegian schools that were enrolled in the European Network of Health-Promoting Schools from 1993 to 2003. The research questions were: How do the principals perceive that health-promoting practices have been sustained in the schools following the schools' membership of the health-promoting schools network? In what way is school leadership related to the sustainability of health promotion? The study draws on qualitative da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 26 publications
(30 reference statements)
2
33
0
Order By: Relevance
“…With regard to the school-leader-oriented influencing factors, our results confirm the findings of previous studies [19][20][21][22]. HPS attitudes and competencies served as significant predictors for HPS implementation for both male and female school leaders.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…With regard to the school-leader-oriented influencing factors, our results confirm the findings of previous studies [19][20][21][22]. HPS attitudes and competencies served as significant predictors for HPS implementation for both male and female school leaders.…”
Section: Discussionsupporting
confidence: 89%
“…Personal knowledge and professional experiences had an influence on the decision-making process, i.e., often school principals with active participation in school health promotion had a professional background as physical education, biology, or psychology teacher. Evidence from the Norwegian Network on Health Promoting Schools suggests that a positive attitude of the school leader towards school health promotion was perceived as key for running the program at schools and for sustaining it over time [20,21]. Moreover, current research results from Taiwan with n = 1.140 school principals and n = 1.110 HPS coordinators (i.e., teachers) indicate that school leaders' understanding of the HPS and their willingness to sustain HPS at their school were significantly associated with higher levels of HPS implementation and teachers' willingness to implement HPS on a continuing basis [22].…”
Section: Introductionmentioning
confidence: 99%
“…This also highlights the importance of teacher and staff support and involvement for the initiative, another important core condition revealed in the present analysis as well as in Langford et al’s review [40]. Previous research has found that principals perceived teachers’ competence and understanding as an invaluable component of CSH, whereby motivated teachers were central to the perpetuation and maintenance of the initiative [47]. This sentiment was reiterated in the present analysis, as emphasized from the viewpoints of several school stakeholders, not just the principal.…”
Section: Discussionsupporting
confidence: 71%
“…This interpretation is supported by previous findings from a case study applying mixed methods in one of the schools, indicating that an extended physical activity practice was sustained in the case study school during the 10-year study period due to the ability of the principal and program manager to establish collaboration and commitment in the staff, and to ensure that their staff was given rewarding experiences and increased competence in the promotion of physical activity [29]. Another 14 year follow-up study of the sustainability of health promoting practices in seven of the schools in the Norwegian Network of HPS, also suggested that the leaders who had a strong, continued and systematic focus on health promotion increased the possibility for teachers to participate in the program [57].…”
Section: School and Program Leadershipmentioning
confidence: 99%